Clinical and epidemiological features of tibial tubercle avulsion fracture in Chinese adolescents - Dahui Wang; Yueqiang Mo (BMJ Publishing Group, 2020)
Background Tibial tubercle avulsion fracture is rare in children. Accumulated knowledge on clinical and epidemiological features of this fracture is of practical significance for clinical colleagues to deal effectively with such fractures.Methods Clinical and epidemiological parameters were reviewed retrospectively in 29 patients with tibial tubercle avulsion fracture that was treated in our hospital in the past 7 years.Results Totally, 29 children with 30 tibial tubercle fractures were enrolled. They were all boys; the average age was 13.8 (12-15) years, and the average Body Mass Index (BMI) was 26.4 (19.2-34.3). Statistically, 41.4% of injuries occurred during jumping activities, and 1 (3.4%), 12 (41.4%) and 16 (55.2%) patients were injured bilaterally, on the right and left sides, respectively. The patients were classified into type I (4), II (3), III (13) and IV (10) fractures. Two patients (three knees) with fractures of type IV received close reduction and cast immobilization for 6 weeks. One patient with fracture of type IV underwent close reduction and was fixed with two cannulated screws. The remaining 26 patients underwent open reduction and were fixed with two or three cannulated screws. The average follow-up time was 38 (14-98) months; no complication was noted. Twenty-seven patients had an excellent outcome.Conclusion In Chinese adolescents, the tibial tubercle avulsion fracture predisposes to boys with higher body weight; jumping is the most common cause of injury; treatments show satisfactory outcome regardless of fracture types.